Weight-Loss Induced Changes in Plasma Factor VII Coagulant Activity and Relation to the Factor VII Arg/Gln353 Polymorphism in Moderately Obese Adults - Pankow, James S.; Folsom, Aaron R.; Shahar, Eyal; Tsai, Michael Y.; Jeffery, Robert W.; Wing, Rena R. (Thrombosis and Haemostasis, 1998)
Elevated plasma factor VII coagulant activity (factor VIIc) may be an independent risk factor for coronary heart disease. Several cross-sectional studies suggest that a polymorphism of the factor VII gene (ArgGln353) interacts with plasma triglyceride level in determining factor VIIc, but prospective data are lacking. Factor VII genotype, factor VIIc, and triglyceride level were measured in moderately obese adults aged 25 to 45 who underwent a six-month clinical trial to evaluate strategies for weight loss. A total of 48 men and 50 women who experienced substantial weight loss (mean: 10 kg) provided samples for genetic analysis. Overall, 78% of participants were homozygous for the Arg353 allele, while the remaining 22% were heterozygous (Arg/Gln353). At the baseline examination, heterozygotes had lower mean factor VIIc than Arg353 homozygotes (92% vs. 112%; p<0.001), and genotype explained 18% of the variance of factor VIIc. Average six-month weight loss was similar in both genotypes; mean reductions in factor VIIc following weight loss were greatest among Arg353 homozygotes with high initial values (>120%). Cross-sectional and longitudinal associations between plasma factor VIIc and triglyceride level were not dependent on genotype. These data confirm that the Gln353 allele is associated with lower factor VII coagulant activity in moderately obese adults, but they do not support the hypothesis that the Arg-Gln353 polymorphism interacts with plasma triglyceride level in determining factor VIIc.